Republic of Belarus : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
This Selected Issues Paper presents an analysis of Belarus-specific conditions and cross-country research, and proposes a roadmap for real-sector reforms. It highlights distortions resulting from the government's interference in the economy, and presents an overview of economic benefits of deregulation, labor market liberalization, and enterprise reform. The paper also provides estimates of potential gains for Belarus from conducting structural reforms, and offers a blueprint for restructuring while minimizing the risks of resource dislocation.